Levelized Product Cost: Concept and Decision Relevance - Stefan Reichelstein; Anna Rohlfing-Bastian (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper examines a life-cycle cost concept that applies to both manufacturing and service industries in which upfront capacity investments are essential. Borrowing from the energy literature, we refer to this cost measure as the levelized product cost (LC). Per unit of output, the levelized cost aggregates a share of the initial capacity expenditure with periodic fixed and variable operating costs. The resulting cost figure exceeds the full cost of a product, as commonly calculated in managerial accounting. Our analysis shows that the LC can be interpreted as the long-run marginal product cost. In particular, this cost measure is shown to be the relevant unit cost that firms should impute for investments in productive capacity.
Keywords: M20; M41; L11; L12; 330